Textiles a world tour discovering traditional fabrics and patterns - Legrand, Catherine (London Thames and Hudson, 2012)
New in paperback, this colourful book takes the reader on an international textile tour with a fabric-collecting fashion designer. Pieced together much like the fine garments it portrays, this book presents in glorious photographs, samples and sketches a raft of remarkable clothing from all over the world. Taking the reader from Vietnam to Benin, from Central America to northern India, the book is brimful of stunning costumes, vibrant fabrics and breathtaking detail. All designers and anyone who loves fashion will find this volume a huge source of inspiration, as will all fans of off-the beaten-track travel destinations.
Keywords: Textile fabrics; Textile design; Ethnic costume; Clothing and dress